Significance of Spousal Consent in a Loan Agreement as The Enforcement of Joint Asset Provisio - Anne Guntari, Tifauni; Setyorini, Hening Hapsari (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Joint asset causes legal consequences in entering into a loan agreement and its accessor, collateral agreement. These legal consequences shall arise as spousal consent is necessary in entering into such agreement. However, many collateral agreements are arranged without a spousal consent. The purpose of this writing to find out the legal consequences of collateral agreements which are entered into only by one of the parties, husband or wife, over the joint assets and responsibility(s) of the Notary Public and Land Deed Official Certifier (“Pejabat Pembuat Akta Tanah/ PPAT”) regarding the agreement. This study utilizes normative juridical approach which was carried out by examining data from legal norms in the society, including laws and regulations. Based on its characteristic, this research is a descriptive study. The result of this study is agreement remains binding on the joint asset despite the collateral agreement being entered into without spousal consent. Meanwhile, the responsibility of the Notary Public and PPAT if they are proven to neglect their obligation is considered unlawfulacts.